Novel OBP genes similar to hamster Aphrodisin in the bank vole, Myodes glareolus - Stopková, Romana; Zdráhal, Zbynek; Ryba, Stepán; Sedo, Ondrej; Sandera, Martin; Stopka, Pavel (BMC genomics, 2010)
BACKGROUND: Chemical communication in mammals involves globular lipocalins that protect and transport pheromones during their passage out of the body. Efficient communication via this protein - pheromone complex is essential for triggering multiple responses including aggression, mate choice, copulatory behaviour, and onset and synchronization of oestrus. The roles of lipocalins in communication were studied in many organisms and especially in mice (i.e. Mus musculus domesticus) which excrete Major Urinary Proteins (Mup) in excessive amounts in saliva and urine. Other mammals, however, often lack the genes for Mups or their expression is very low. Therefore, we aimed at characterization of candidate lipocalins in Myodes glareolus which are potentially linked to chemical communication. One of them is Aphrodisin which is a unique lipocalin that was previously described from hamster vaginal discharge and is known to carry pheromones stimulating copulatory behaviour in males. RESULTS: Here we show that Aphrodisin-like proteins exist in other species, belong to a group of Odorant Binding Proteins (Obp), and contrary to the expression of Aphrodisin only in hamster genital tract and parotid glands of females, we have detected these transcripts in both sexes of M. glareolus with the expression confirmed in various tissues including prostate, prepucial and salivary glands, liver and uterus. On the level of mRNA, we have detected three different gene variants. To assess their relevance for chemical communication we investigated the occurrence of particular proteins in saliva, urine and vaginal discharge. On the protein level we confirmed the presence of Obp2 and Obp3 in both saliva and urine. Appropriate bands in the range of 17-20 kDa from vaginal discharge were, however, beyond the MS detection limits. CONCLUSION: Our results demonstrate that three novel Obps (Obp1, Obp2, and Obp3) are predominant lipocalins in Myodes urine and saliva. On the protein level we have detected further variants and thus we assume that similarly as Major Urinary Proteins in mice, these proteins may be important in chemical communication in this Cricetid rodent.
Keywords: proteiny; Male; Saliva; 2D gelová elektroforéza; tandemová hmotnostní spektrometrie; molekulární sekvence - údaje; Amino Acid Sequence; Electrophoresis, Gel, Two-Dimensional; mužské pohlaví; stanovení celkové genové exprese; sekvenční seřazení; Gene Expression Profiling; Receptors, Odorant; moč; Animals; lipokaliny; ženské pohlaví; Urine; receptory pachové; zvířata; Arvicolinae; sekvence aminokyselin; spektrometrie hmotnostní - ionizace laserem za účasti matrice; sliny; Molecular Sequence Data; Lipocalins; Pheromones; Tandem Mass Spectrometry; Female; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Vagina; vagina; Proteins; feromony; Sequence Alignment